2023
DOI: 10.1371/journal.pbio.3001999
|View full text |Cite
|
Sign up to set email alerts
|

Alpha oscillatory activity is causally linked to working memory retention

Abstract: Although previous studies have reported correlations between alpha oscillations and the “retention” subprocess of working memory (WM), causal evidence has been limited in human neuroscience due to the lack of delicate modulation of human brain oscillations. Conventional transcranial alternating current stimulation (tACS) is not suitable for demonstrating the causal evidence for parietal alpha oscillations in WM retention because of its inability to modulate brain oscillations within a short period (i.e., the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…A recent modeling study suggested that TI can affect the human hippocampus ( Lee et al, 2020 ), and an investing study claimed that TI could be safe and well tolerated in human participants ( Piao et al, 2022 ). The other development is closed-loop tACS, which has significant potential for treating neurological and psychiatric disorders with irregular patterns ( Chen et al, 2023 ). Recent studies have indicated that the effect of tACS is influenced by the state of the ongoing brain oscillations ( Krause et al, 2022 ).…”
Section: Advances In Tacs Methodsmentioning
confidence: 99%
“…A recent modeling study suggested that TI can affect the human hippocampus ( Lee et al, 2020 ), and an investing study claimed that TI could be safe and well tolerated in human participants ( Piao et al, 2022 ). The other development is closed-loop tACS, which has significant potential for treating neurological and psychiatric disorders with irregular patterns ( Chen et al, 2023 ). Recent studies have indicated that the effect of tACS is influenced by the state of the ongoing brain oscillations ( Krause et al, 2022 ).…”
Section: Advances In Tacs Methodsmentioning
confidence: 99%
“…The con�nuous phase-tuning in our approach naturally results in a con�nuous frequency-tuning, as a constant phase difference between two signals implies that they have iden�cal frequency [41]. transform was applied to the data to remove broadband s�mula�on ar�facts and obtain a real-�me phase es�mate of parieto-occipital alpha oscilla�ons (8)(9)(10)(11)(12)(13)(14). (E) The real-�me phase es�mate of alpha oscilla�ons was incremented by φ to obtain the phase of the CLAM-tACS envelope signal.…”
Section: Real-�me Eeg Processingmentioning
confidence: 99%
“…Yet, several studies have also demonstrated a connection between alpha waves and working memory. For example, alpha oscillations were persistently observed during working memory retention (see Roux & Uhlhaas, 2014 for review), and causally linked to this process (Chen et al, 2023; Riddle et al, 2020; Sauseng et al, 2009). Moreover, experimental findings revealed that alpha power increased with working memory load (Jensen et al, 2002) and with anticipated distractors (Bonnefond & Jensen, 2012; Payne et al, 2013), suggesting that alpha oscillations may be involved in protecting memory maintenance through an inhibitory mechanism.…”
Section: Introductionmentioning
confidence: 99%